Awareness regarding hypertension complications among hypertensive patients attending Kalar General Hospital in Sulaimaniyah province of Iraq - Hussein, Rahman Othman; Muhammed, Omed Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Hypertension complications are amongst the principal cause of admission in most healthcare facilities worldwide. Unawareness of hypertension complications increases morbidity and mortality rate. Patients' awareness regarding hypertension and its complications plays an important role in preventing or delaying the relevant events. Objectives: To assess the awareness toward hypertension-related complications in patients with hypertension. Patients and methods: A quantitative-descriptive crosssectional study was conducted in Kalar General Hospital in Kalar city from May 2022 to January 2023. About 250 patients with hypertension consented to participate in the study. Non-probability convince sampling method was used to select the participants. The data were collected through a questionnaire by direct interview. Results: Most patients were aged between (40-65 years), females, married, housewives, illiterate, and lived in an urban area. The study's findings revealed insufficient awareness in >50% of patients. A highly significant correlation between awareness and the level of education has been founded and also a significant association with age, gender, and profession was found. While marital status and residency didn’t affect the awareness. Conclusions: More than three quarter of patients were not aware or had inadequate awareness of hypertension complications.
Keywords: Awareness; hypertension; complication